Number one is walking my life in the movies and other diversions - Martin, Steve 1945-; Bliss, Harry, 1964- (New York Celadon Books, 2022)
"Number One Is Walking is Steve Martin's cinematic legacy-an illustrated memoir of his legendary acting career, with stories from his most popular films and artwork by New Yorker cartoonist Harry Bliss. Steve Martin has never written about his career in the movies before. In Number One Is Walking, he shares anecdotes from the sets of his beloved films-Father of the Bride, Roxanne, The Jerk, Three Amigos, and many more-bringing readers directly into his world. He shares charming tales of antics, moments of inspiration, and exploits with the likes of Paul McCartney, Diane Keaton, Harrison Ford, and Chevy Chase. Martin details his forty years in the movie biz, as well as his stand-up comedy, banjo playing, writing, and cartooning, all with his unparalleled wit. With gorgeously illustrated cartoons and single-panel "diversions" in Steve and Harry's signature style, Number One Is Walking is full of the everyday moments that make up a movie star's life, capturing Steve Martin's singular humor and acclaimed career in film. The perfect gift from the team who brought you the #1 New York Times bestseller A Wealth of Pigeons"--
Keywords: Martin, Steve, -- 1945- -- Comic books, strips, etc; Motion picture actors and actresses -- United States -- Biography -- Comic books, strips, etc; Comedians -- United States -- Biography -- Comic books, strips, etc; United States; Comics (Graphic works); Autobiographical comics; Nonfiction comics; Graphic novels